Impact of Scene Features of E-Commerce Live Streaming on Consumers’ Flow and Purchase Intentions of Sporting Goods - Zhengyu Li; Yan Wang; Beth Anne Cianfrone; Zhen Guo; Bo Liu; James Zhang; Chenyu Shi (Behavioral Sciences, 2025)
Purpose—The purpose of this study is to examine the mechanism of scene features (i.e., visual appeal, presence, and scene–product matching) of e-commerce live streaming and how it impacts consumers’ flow and purchase intentions of sporting goods. Design/methodology/approach—To test the hypotheses in the conceptualized model that was developed based on the Stimulus–Organism–Response (S-O-R) model, sports consumers (N = 340) who watched e-commerce live streaming responded to an online survey administration. Structural equation modeling (SEM) was applied to examine the research model and test the hypotheses. Findings—The results reveal that scene features positively affect consumer flow experience, in which scene–product matching is the main contributing factor. Moreover, the flow experience plays a critical mediating role in influencing purchase intentions; meanwhile, the moderation role of sport identification was not found to be statistically significant. Originality/value—This study fills the void to explore how scene features of e-commerce live streaming influence consumer behavior associated with sporting goods merchandise through immersed flow experience. Confirming the applicability of the S-O-R model in the sports e-commerce live streaming setting, the findings of this study identify dimensions of scene features of e-commerce live streaming and highlight the significance of developing scene–product congruence features when designing, operating, and promoting live streaming programs while enhancing immersive involvement.